Gel solid electrolyte, lithium ion battery and preparation method

By using gel solid electrolyte and ceramic layer structure in lithium batteries, the problems of thermal runaway and increased separator thickness of lithium batteries are solved, and the self-extinguishing and safety performance of the battery are improved.

CN119764548APending Publication Date: 2025-04-04WANXIANG 123 CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510007543.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

High-energy density lithium batteries are prone to fire or explosion when thermally out of control. The increase in thickness of the existing diaphragm coating leads to an increase in internal resistance, affecting battery performance.

Method used

A gel solid electrolyte is used to polymerize through polymer monomer initiator, a flame retardant additive is added to achieve self-extinguishing performance, and a ceramic layer is formed in the separator to enhance the mechanical strength and isolation effect.

Benefits of technology

It effectively avoids direct or indirect contact between the positive electrode and the negative electrode of the lithium battery at high temperatures, prevents thermal runaway, and ensures the safety and electrical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764548A_ABST
    Figure CN119764548A_ABST
Patent Text Reader

Abstract

The present invention discloses a gel solid electrolyte, a battery and a preparation method, and belongs to the technical field of lithium ion batteries. A gel solid electrolyte precursor, according to the mass fraction, the raw materials include: 2-7 parts of polymer monomer; 60-85 parts of solvent; 1-7 parts of flame retardant additive; 10-15 parts of lithium salt; 0.1-1 parts of initiator. The gel solid electrolyte provided by the present invention is solidified by the precursor and has self-extinguishing properties. When applied to lithium ion batteries, it can effectively avoid direct contact or gas transmission between the positive and negative electrodes of the lithium battery at high temperatures, thereby avoiding the occurrence of thermal runaway of the lithium battery. Compared with liquid electrolytes, the gel solid electrolyte provided by the present invention achieves the effect of self-extinguishing and isolating the positive and negative electrodes with a lower proportion of flame retardant additives, thereby ensuring the safety and electrical performance of lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a gel solid electrolyte, a battery and a preparation method thereof. Background Art

[0002] Lithium battery thermal runaway refers to the phenomenon that when a lithium battery is subjected to external physical damage, overcharge, short circuit or other abnormal operation, the internal temperature rises rapidly and causes a series of uncontrollable chemical reactions, which may eventually cause a fire or explosion. The potential risk of thermal runaway of lithium batteries limits their application as automotive power batteries.

[0003] In a high-energy-density lithium battery system, the conversion of chemical energy stored in the positive and negative electrode materials into thermal energy is the fundamental reason for the overall thermal runaway of the battery. The conversion of chemical energy into thermal energy is caused by direct or indirect contact between the positive and negative electrode materials. Direct contact refers to the melting and shrinkage of the diaphragm, which causes physical contact and internal short circuits over large positive and negative areas; indirect contact refers to the early stage of thermal runaway when the diaphragm is still intact, when the oxygen released by the thermal decomposition of the positive electrode passes through the diaphragm and triggers a redox reaction at the negative electrode, resulting in continuous heating of the battery and side reactions.

[0004] In order to improve the thermal runaway stability of high-energy-density lithium batteries, CN116666901A discloses a diaphragm coating slurry containing ammonium polyphosphate, polyacrylic acid and metal oxide. The cross-linked product of ammonium polyphosphate and polyacrylic acid improves the mechanical strength of the diaphragm, allowing the PP diaphragm to not melt when baked at 300°C. At the same time, the metal oxide improves the puncture resistance of the diaphragm and alloys with the lithium metal negative electrode in the battery to form a stable passivation layer. However, the addition of an additional coating layer will increase the thickness of the diaphragm, resulting in an increase in internal resistance, which will affect the performance of the battery. Summary of the invention

[0005] The object of the present invention is to provide a gel solid electrolyte with self-extinguishing properties without additionally increasing the thickness of the diaphragm; another object of the present invention is to provide a safer gel solid lithium ion battery that can inhibit direct or indirect contact between the positive electrode and the negative electrode; another object of the present invention is to provide a method for preparing a safer lithium ion battery.

[0006] The present invention provides a gel solid electrolyte precursor, which is characterized by comprising raw materials, in terms of mass fractions:

[0007]

[0008] The polymer monomer is polymerized into gel by an initiator, and the flame retardant additive in the gel solid electrolyte makes it have the property of self-extinguishing.

[0009] The function of the initiator is to initiate chain reaction polymerization between polymer monomer molecules, mainly including peroxide initiators, azo initiators, etc.

[0010] Peroxide initiators include dibenzoyl peroxide, di-tert-butyl peroxide, and cumene hydroperoxide.

[0011] Azo initiators include azobisisobutyronitrile, azobisisoheptanenitrile, etc.

[0012] The solvent may be selected from the solvents used in conventional lithium ion electrolytes, such as carbonate solvents, carboxylate solvents, ether solvents, sulfone and sulfoxide solvents, and fluorinated solvents.

[0013] Carbonate solvents include ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate and the like.

[0014] Carboxylic acid ester solvents include γ-butyrolactone, ethyl acetate, and the like.

[0015] Ether solvents include tetrahydrofuran, 1,3-dioxolane, 1,2-dimethoxyethane and the like.

[0016] Sulfone and sulfoxide solvents include sulfolane, methylbenzothiazole sulfoxide, etc.

[0017] Fluorinated solvents include fluoroethylene carbonate, bissulfone and sulfoxide solvents.

[0018] The polymer monomers include one or at least two of unsaturated ethers, unsaturated nitriles, unsaturated carbonates, unsaturated acid anhydrides, and unsaturated silanes.

[0019] The lithium salt may be a lithium salt used in conventional lithium ion electrolytes, such as lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonylimide), lithium difluorooxalatoborate, lithium bis(fluorosulfonylimide) and the like.

[0020] Further, the polymer monomer includes one or at least two of triethylene glycol dimethacrylate, ethylene glycol diacrylate, methoxy polyethylene glycol acrylate, (propylene glycol) methacrylate, (propylene glycol) dimethacrylate, ethylene glycol methyl ether methacrylate, ethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, acrylonitrile, allyl cyanide, 4-pentenenitrile, perfluoroalkylethyl methacrylate, 2,2,3,4,4,4-hexafluorobutyl methacrylate, 2,2,3,3,4,4,4-heptafluorobutyl acrylate, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate, and 2-(perfluorooctyl)ethyl methacrylate.

[0021] Further, the flame retardant additive includes one or at least two of phenoxy cyclophosphazene, hexafluorocyclotriphosphazene, ethoxy (pentafluoro) cyclotriphosphazene, pentafluoro (phenoxy) cyclotriphosphazene, trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, 4-isopropylphenyl diphenyl phosphate, diphenyl octyl phosphate, and trioctyl phosphate.

[0022] The raw materials of the gel solid electrolyte precursor include, by weight:

[0023]

[0024]

[0025] The invention also discloses a gel solid electrolyte, which is formed by initiating polymerization of the gel solid electrolyte precursor described above.

[0026] The present invention also discloses a gel solid-state lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and the gel solid-state electrolyte as described above.

[0027] Furthermore, the diaphragm includes a polymer layer and a ceramic layer coated on both sides of the polymer layer.

[0028] The polymer layer includes polymers commonly used in lithium-ion battery separators, such as PP, PE, PVDF, PI, aramid, etc.

[0029] Before solidification, the gel solid electrolyte will infiltrate into the pores of the ceramic layer and the polymer layer. After solidification, the gel solid electrolyte is distributed in the pores of the ceramic layer and the polymer layer. On the one hand, the gel solid electrolyte eliminates the air permeability of the diaphragm by solidifying in the pores of the polymer layer and the ceramic layer, which has an isolating effect on the oxygen released by the positive electrode and inhibits the indirect contact between the positive and negative electrodes; on the other hand, the ceramic layer plays a role in improving the mechanical strength of the diaphragm. Above the melting temperature of the polymer layer, it avoids the shrinkage of the gel solid electrolyte due to the shrinkage of the polymer layer, thereby inhibiting the direct contact between the positive and negative electrodes; thirdly, the flame retardant components inside the gel solid electrolyte prevent the combustion of the electrolyte itself, and can capture oxygen free radicals, improving the intrinsic safety of the gel solid electrolyte.

[0030] Furthermore, the thickness of a single side of the ceramic layer is 3-5 μm; the material of the ceramic layer includes one or at least two of aluminum oxide, boehmite, titanium oxide, perovskite-type LLTO solid electrolyte, and garnet-type LLZO solid electrolyte.

[0031] The present invention also discloses a method for preparing a gel solid-state lithium-ion battery, comprising the following steps:

[0032] S1. Assemble the positive electrode sheet, negative electrode sheet and separator of the lithium-ion battery into a dry cell, and inject the gel solid electrolyte precursor as described above into the dry cell;

[0033] S2: The dry battery cell injected with the gel solid electrolyte precursor is heated and cured to obtain a gel solid lithium-ion battery.

[0034] Furthermore, in step S2, the heating curing is performed at 55-65° C. and the curing time is 22-26 hours.

[0035] After the gel solid electrolyte precursor is injected into the dry battery cell, it will infiltrate into the pores inside the positive electrode sheet, the pores inside the negative electrode sheet, and the pores between the packaging layer and the bare cell. After solidification, it will fill the pores, thereby improving the safety performance of the lithium-ion battery.

[0036] The gel solid electrolyte provided by the present invention has self-extinguishing properties, and when applied to lithium-ion batteries, it can effectively avoid direct contact or gas transmission between the positive and negative electrodes of the lithium battery at high temperatures, thereby avoiding the occurrence of thermal runaway of the lithium battery. Compared with liquid electrolytes, the gel solid electrolyte provided by the present invention achieves the effects of self-extinguishing and isolating the positive and negative electrodes with a lower ratio of flame retardant additives, thereby ensuring the safety and electrical performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a hot box test curve diagram of the lithium ion battery prepared in Example 3 of the present invention;

[0038] Figure 2 This is a hot box test curve diagram of the lithium ion battery prepared in Example 5 of the present invention;

[0039] Figure 3 This is a diagram of the open flame ignition experiment process of the gel solid electrolyte after disassembly of the lithium ion battery prepared in Example 3 of the present invention;

[0040] Figure 4 This is a diagram of the open flame ignition experiment process of the disassembled diaphragm of the lithium-ion battery prepared in Example 3 of the present invention;

[0041] Figure 5 This is a diagram of the open flame ignition experiment process of the boehmite|PE|boehmite (3+9+3μm) diaphragm;

[0042] Figure 6 It is a diagram of the open flame ignition experiment process of the diaphragm after disassembly of the lithium-ion battery prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0043] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0044] Example 1

[0045] The soft pack battery in this embodiment is prepared by the following method:

[0046] (1) Preparation of negative electrode sheet:

[0047] The negative electrode active material (graphite + silicon oxide, mass ratio 93.5:6.5), conductive agent (carbon black), binder (styrene-butadiene rubber + sodium carboxymethyl cellulose, mass ratio 1:1) were dispersed in water at a mass ratio of 97:1:2 to obtain a uniformly dispersed negative electrode slurry. The negative electrode slurry was coated on copper foil with a coating surface density of 170g / m 2 , baking, rolling, slitting and punching to obtain the negative electrode sheet.

[0048] (2) Preparation of positive electrode sheet:

[0049] The positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive agent (carbon black), and binder (polyvinylidene fluoride) are dispersed in N-methylpyrrolidone at a mass ratio of 96:2:2 to obtain a uniformly dispersed positive electrode slurry. The positive electrode slurry is coated on the composite current collector foil with a coating surface density of 350g / m 2 , baking, rolling, slitting and punching to obtain the positive electrode sheet.

[0050] (3) Dry cell assembly:

[0051] The positive electrode sheets and negative electrode sheets prepared above were stacked using boehmite|PE|boehmite (3+9+3μm) separators to prepare soft-pack batteries, and the theoretical capacity of the battery cell was 6.3Ah.

[0052] (4) Dry cell injection precursor and curing:

[0053] The moisture content in the glove box is controlled to be no more than 10 ppm, ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate are stirred and mixed uniformly in a mass ratio of 30 / 5 / 45 / 20, and purified and decontaminated with molecular sieves to obtain a solvent component.

[0054] In a glove box, ethoxylated trimethylolpropane triacrylate and acrylonitrile were mixed in a mass ratio of 9:1 to remove the polymerization inhibitor using neutral alumina as a polymer monomer component; trimethyl phosphate as a flame retardant additive component; lithium hexafluorophosphate as a lithium salt component; and azobisisobutyronitrile as an initiator component. The polymer monomer, solvent, flame retardant additive, lithium salt, and initiator were mixed in a mass ratio of 5 / 77 / 5 / 12.5 / 0.5 and stirred until clear to obtain a gel solid electrolyte precursor.

[0055] In a protective atmosphere with a moisture and oxygen content of no more than 10 ppm, a gel solid electrolyte precursor is injected into a dry battery cell, and a gel solid lithium-ion soft-pack battery is obtained after heating and curing at 60°C for 24 hours.

[0056] Example 2

[0057] Compared with Example 1, the difference of Example 2 is that the polymer monomer, the solvent, the flame retardant additive, the lithium salt, and the initiator are mixed in a mass ratio of 5 / 78 / 4 / 12.5 / 0.5.

[0058] Example 3

[0059] Compared with Example 1, the difference of Example 3 is that the polymer monomer, the solvent, the flame retardant additive, the lithium salt, and the initiator are mixed in a mass ratio of 5 / 79 / 3 / 12.5 / 0.5.

[0060] Example 4

[0061] Compared with Example 3, the difference of Example 4 is that LATP|PE|LATP (3+9+3 μm) separator is used in the dry cell assembly process.

[0062] Example 5

[0063] Compared with Example 3, the difference of Example 5 is that a boehmite|PE|LATP (3+9+3 μm) separator is used in the dry cell assembly process, wherein the boehmite coating is for the negative electrode and the LATP coating is for the positive electrode.

[0064] Example 6

[0065] Compared with Example 3, the difference of Example 6 is that the additive is triphenyl phosphate.

[0066] Example 7

[0067] Compared with Example 3, the difference of Example 7 is that the additive is ethoxy (pentafluoro) cyclotriphosphazene.

[0068] Example 8

[0069] Compared with Example 3, the difference of Example 8 is that the polymer monomer, the solvent, the flame retardant additive, the lithium salt, and the initiator are mixed in a mass ratio of 5 / 80 / 2 / 12.5 / 0.5.

[0070] Comparative Example 1

[0071] Compared with Example 3, the difference in Comparative Example 1 is that a boehmite|PE|boehmite (2+9+2 μm) separator is used in the dry cell assembly process.

[0072] Comparative Example 2

[0073] Compared with Example 3, the difference of Comparative Example 2 is that a boehmite|PE|boehmite (3+9+2 μm) separator is used in the dry cell assembly process, wherein the 3 μm boehmite coating is applied to the negative electrode.

[0074] Comparative Example 3

[0075] Compared with Example 3, the difference of Comparative Example 3 is that a boehmite|PE|boehmite (2+9+3 μm) separator is used in the dry cell assembly process, wherein the 2 μm boehmite coating is applied to the negative electrode.

[0076] Comparative Example 4

[0077] Compared with Example 3, the difference of Comparative Example 4 is that no polymer monomer and initiator component are added, and the solvent, flame retardant additive and lithium salt are mixed in a mass ratio of 82.5 / 5 / 12.5.

[0078] Comparative Example 5

[0079] Compared with Example 3, the difference of Comparative Example 5 is that no polymer monomer and initiator component are added, and the solvent, flame retardant additive and lithium salt are mixed in a mass ratio of 72.5:15:12.5.

[0080] Performance testing and result analysis:

[0081] 1. Electrical performance test of gel solid-state lithium-ion battery

[0082] The gel solid-state lithium-ion soft-pack batteries prepared in Examples 1-8 and Comparative Examples 1-5 were charged at 25°C at 0.1C constant current to 4.25V, and at 4.25V constant voltage to 0.05C to obtain a 0.1C first charge capacity Q FCC (Ah); discharge to 2.8V at 0.1C constant current, and obtain 0.1C constant capacity Q FDC (Ah); then charged to 4.25V at 0.3C constant current, charged to 0.05C at 4.25V constant voltage, then discharged to 2.8V at 0.3C constant current, and obtained 0.3C constant capacity Q 2nd grading (Ah). Then charge at 0.3C constant current for 1h to 30% SOC. After standing for half an hour, record the battery steady-state voltage U0 (V), then discharge at 2.5C rate for 10s to obtain the battery voltage U1 (V0). Then charge at 0.3C constant current to 4.25V, charge at 4.25V constant voltage to 0.05C, then discharge at 0.3C constant current to 2.8V. After 100 cycles, obtain the capacity Q 100cycles (Ah).

[0083] Coulombic efficiency ICE (%) = QFDC / Q FCC *100%;

[0084] Battery offline DCR (mΩ) = (U1-U0) / 2.5 / 6.3*1000;

[0085] Battery 100 cycle capacity retention rate (%) = (Q 100 cycles / Q 2nd grading )*100%, the relevant test results are shown in Table 1.

[0086] Table 1 Test results of gel solid lithium ion soft pack batteries prepared in Examples and Comparative Examples

[0087]

[0088]

[0089] As shown in Table 1, the test results of Examples 1-5 show that as the content of the flame retardant additive decreases, the coulombic efficiency ICE and capacity utilization of the battery are significantly increased, and the DCR is significantly reduced. This is due to the high viscosity of the flame retardant additive and the property of easily reacting with the negative electrode, which reduces the capacity retention rate of the corresponding battery. Comparing Examples 4 and 5, the boehmite in the ceramic coating of the diaphragm is replaced by the fast ion conductor LATP, which can reduce the internal resistance of the solid-state battery, but the side reaction between LATP and the negative electrode will significantly reduce the ICE of the battery. As shown in the data of Example 4, using LATP on one side of the positive electrode can effectively improve the capacity utilization and avoid ICE decline, as shown in the data of Example 5, and does not significantly reduce the cycle stability of the battery.

[0090] As shown in Example 1, Examples 6-8 and Comparative Examples 1-3, under the same flame retardant additive ratio, the gel solid-state lithium-ion battery using trimethyl phosphate has lower internal resistance and higher battery cycle stability, while triphenyl phosphate (Example 6) and ethoxy (pentafluoro) cyclotriphosphazene (Example 7) have greater effects on electrolyte viscosity and battery performance due to the presence of the cyclic structure. Further reducing the flame retardant additive ratio (Example 8) and lowering the thickness of the ceramic layer (Comparative Examples 1-3) can partially reduce the internal resistance of the solid-state battery, but other performance improvements are not obvious.

[0091] By comparing Example 1 and Comparative Examples 4-5, it can be seen that at the same flame retardant ratio, the liquid battery has a higher capacity, lower impedance and higher ICE. The improvement of ICE compared to the solid-state battery is mainly due to the fact that after the gel solidifies between the negative electrode main material particles, part of the gel deforms as the negative electrode particles expand after the first charge, and cannot maintain contact with the main material during the discharge process, resulting in capacity loss. However, the lack of gel constraints and the uninhibited reaction between the flame retardant additive and the negative electrode interface result in the cycle stability of the liquid battery being inferior to that of the gel solid-state battery. When the flame retardant additive ratio is too high (Comparative Example 5), it will cause serious interface side reactions and increase the viscosity of the electrolyte, further affecting the performance of the liquid battery.

[0092] 2. Hot box safety test

[0093] The formed battery is charged to 4.25V at 0.3C constant current and 0.05C constant voltage, and then subjected to hot box test. The test steps are as follows:

[0094] Store the battery at 60℃ for 150min; increase the temperature to 130℃ at 5℃ / min and keep warm for 30min; increase the temperature to 150℃ at 2℃ / min and keep warm for 30min; increase the temperature to 170℃ at 2℃ / min and keep warm for 30min; increase the temperature to 190℃ at 2℃ / min and keep warm for 30min; stop heating and store for 60min or the battery temperature drops below 50℃.

[0095] Battery cell thermal runaway temperature (℃): The battery cell temperature when the corresponding voltage drops to 4.00V.

[0096] The relevant test results are shown in Table 2 and Figure 1-2 shown.

[0097] Table 2 Hot box test results of gel solid lithium ion soft pack batteries prepared in Examples and Comparative Examples

[0098] Battery Cell Is there thermal runaway? Thermal runaway temperature(℃) Example 3 no / Example 5 no / Example 8 yes 182.4 Comparative Example 1 yes 178.9 Comparative Example 2 yes 175.0 Comparative Example 3 yes 178.3 Comparative Example 4 yes 165.9

[0099] like Figure 1-2 As shown in Table 2, by comparing Example 3 and Example 8, it can be concluded that the gel solid-state lithium-ion battery prepared by using 3wt% or more of trimethyl phosphate as a flame retardant additive in the gel solid-state electrolyte precursor is sufficient to maintain the structural integrity of the solid-state electrolyte above the thermal runaway temperature of the diaphragm polymer layer. A local micro short circuit occurs in the battery cell, which is manifested as a voltage drop, but does not cause a large-scale internal short circuit. After mild discharge and heat release, the battery cell becomes inert, and ultimately no battery thermal runaway occurs ( Figure 1-2 shown).

[0100] From Example 3, Example 5, and Comparative Examples 1 to 3, it can be seen that the ability of the gel solid-state lithium-ion battery to suppress thermal runaway is affected by the thickness of the diaphragm ceramic layer. The hot box safety of the battery cell can only be achieved if the thickness of the ceramic layer on both sides of the polymer layer is greater than or equal to 3μm, and the type of ceramic layer does not affect the technical effect.

[0101] By comparing Example 3 and Comparative Example 4, it can be seen that at a flame retardant additive concentration sufficient to ensure that the gel solid-state lithium-ion battery does not experience thermal runaway, the liquid electrolyte lithium-ion battery still suffers from an internal short circuit. This is caused by the inability of the liquid electrolyte to prevent the "indirect contact" between the positive and negative electrodes. The thermal runaway starting temperature is also significantly lower than that of other solid-state battery packs.

[0102] 3. Open flame ignition experiment

[0103] A dehumidifier was used to control the humidity in an air atmosphere with a dew point of -40°C. The gel solid lithium ion batteries prepared in Example 3 and Comparative Example 1 were disassembled after formation. The gel solid electrolyte, the diaphragm with the gel solid electrolyte filled in the pores, and the boehmite|PE|boehmite diaphragm (3+9+3μm) that had not been assembled into a battery as a comparative example were collected and ignited with a lighter. Optical photos before and after ignition are shown in Figure 1. Figure 3-6 As shown:

[0104] like Figure 3 As shown, the self-extinguishing gel obtained by disassembling Example 3 does not burn or change shape after contacting an open flame. Figure 4 As shown in the figure, the solid electrolyte of the composite boehmite|PE|boehmite diaphragm (3+9+3 μm) filled with gel solid electrolyte in the pores of Example 3 can also be ignited by open flames, but can maintain its original shape and structure after self-extinguishing. Figure 5 As shown in the figure, the boehmite|PE|boehmite separator (3+9+3 microns) that has not been assembled into a battery quickly burns and powders after contacting an open flame. Figure 6 As shown, the self-extinguishing gel and boehmite|PE|boehmite diaphragm (2+9+2 microns) filled with gel solid electrolyte in the pores of comparative example 1 will shrink into a ball quickly after being ignited, and cannot maintain the shape and structure of the diaphragm before. The ceramic layer with a thickness of more than 3μm maintains the stability of the diaphragm structure after heating, which can effectively avoid the occurrence of short circuits in the battery in the actual battery environment, so it is appropriate to control the thickness of the ceramic layer within the range of 3-5μm.

[0105] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A gel solid electrolyte precursor, characterized in that, by weight, Ingredients include:

2. A gel solid electrolyte precursor according to claim 1, characterized in that: The polymer monomers include one or at least two of triethylene glycol dimethacrylate, ethylene glycol diacrylate, methoxypolyethylene glycol acrylate, (propylene glycol) methacrylate, (propylene glycol) dimethacrylate, ethylene glycol methyl ether methacrylate, ethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, acrylonitrile, allyl cyanide, 4-pentenenitrile, perfluoroalkylethyl methacrylate, 2,2,3,4,4,4-hexafluorobutyl methacrylate, 2,2,3,3,4,4,4-heptafluorobutyl acrylate, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate, and 2-(perfluorooctyl)ethyl methacrylate.

3. A gel solid electrolyte precursor according to claim 1, characterized in that: The flame retardant additive includes one or at least two of phenoxy cyclophosphazene, hexafluorocyclotriphosphazene, ethoxy (pentafluoro) cyclotriphosphazene, pentafluoro (phenoxy) cyclotriphosphazene, trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, 4-isopropylphenyl diphenyl phosphate, diphenyl octyl phosphate, and trioctyl phosphate.

4. The gel solid electrolyte precursor according to claim 1, characterized in that, in terms of mass fraction, Ingredients include:

5. A gel solid electrolyte, characterized in that: The solid-state gel electrolyte is prepared by polymerization initiated by the gel solid electrolyte precursor described in any one of claims 1 to 4.

6. A gel solid-state lithium-ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and the gel solid electrolyte as claimed in claim 5.

7. A gel solid lithium ion battery according to claim 6, characterized in that: The diaphragm includes a polymer layer and a ceramic layer coated on both sides of the polymer layer.

8. A gel solid lithium ion battery according to claim 7, characterized in that: The thickness of one side of the ceramic layer is 3-5 μm; the material of the ceramic layer includes one or at least two of aluminum oxide, boehmite, titanium oxide, perovskite-type LLTO solid electrolyte, and garnet-type LLZO solid electrolyte.

9. A method for preparing a gel solid-state lithium-ion battery, characterized in that: The following steps are involved: S1. Assemble the positive electrode sheet, negative electrode sheet and separator of the lithium-ion battery into a dry cell, and inject the gel solid electrolyte precursor as described in any one of claims 1 to 4 into the dry cell; S2: The dry battery cell injected with the gel solid electrolyte precursor is heated and cured to obtain a gel solid lithium-ion battery.

10. The method for preparing a gel solid-state lithium-ion battery according to claim 9, characterized in that: In the step S2, the heating curing is performed at 55-65° C. for 22-26 hours.

Citation Information

Cited By

  • Multi-component in-situ polymerized gel solid electrolyte as well as preparation method and application thereof

    CN120657237A

  • Solid-state battery unit and preparation method of solid-state battery containing composite multifunctional electrolyte layer

    CN120674564A

  • Flame-retardant gel electrolyte, preparation method thereof and lithium ion battery containing electrolyte

    CN121507084A

  • A flame-retardant gel electrolyte, its preparation method, and a lithium-ion battery containing the electrolyte.

    CN121507084B